Analisis ANALISIS COVERAGE AREA JARINGAN 4G LTE TELKOMSEL, XL AXIATA DAN INDOSAT OOREDOO DI KECAMATAN BAYUNG LENCIR, KABUPATEN MUSI BANYUASIN, PROVINSI SUMATERA SELATAN. - Tamsir Ariyadi; Ariyudi Ariyudi (LPPM Universitas Putera Batam, 2022)
The research is to analyze the coverage area of ​​the 4G LTE network of telecommunications operators Telkomsel, XL Axiata, and Indosat Ooredo in Bayung Lencir District, Musi Banyuasin Regency, South Sumatra Province, Indonesia. The information obtained by the result of this research is expected to be useful for the public to determine and choose a telecommunications operator that has the widest coverage area and is a catalyst for improvement for telecommunications operators whose coverage area is not yet wide. This study will analyze the parameters of the 4G LTE network coverage area, namely: Reference Signal Received Power (RSRP) and Signal to Noise Ratio (SINR), on the 4G LTE network. The aim of this study to analyze the coverage area of ​​the 4G LTE network of Telkomsel, XL Axiata and Indosat Ooredoo in Bayung Lencir District, Musi Banyuasin Regency, South Sumatra Province using the G-NetTrack Pro application. The study was conducted in 9 villages/kelurahan in Bayung Lencir District, Musi Banyuasin District, South Sumatra Province. The results of the measurement of the coverage area parameters using the G-NetTrack Pro software were then analyzed statistically with the Single Factor Analysis of Variance. The results of the study, that find RSRP and SINR parameters for cellular operators Telkomsel, XL Axiata, and Indosat Ooredoo, it was found that statistically the RSRP value between operators was not significantly different, which means that the RSRP values ​​for Telkomsel, XL Axiata, and Indosat Ooredoo were considered the same and the SINR parameter for operators Telkomsel, XL Axiata, and Indosat Ooredoo are statistically different where the SINR value of Telkomsel is the highest, followed by Indosat Ooredo at position number 2, and XL Axiata at position 3.